A new indicator for nowcasting employment subject to social security contributions in Germany - Christian Hutter (Journal for Labour Market Research, 2020)
Contrary to the number of unemployed or vacancies, the number of employees subject to social security contribu-tions (SSC) for Germany is published after a time lag of 2 months. Furthermore, there is a waiting period of 6 months until the values are not revised any more. This paper uses monthly data on the number of people subject to compul-sory health insurance (CHI) as auxiliary variable to better nowcast SSC. Statistical evaluation tests using real-time data show that CHI significantly improves nowcast accuracy compared to purely autoregressive benchmark models. The mean squared prediction error for nowcasts of SSC can be reduced by approximately 20%. In addition, CHI outper-forms alternative candidate variables such as unemployment, vacancies and industrial production.
Keywords: C53; E24; E27; J21; 330; Nowcasting; Real-time data; Employees; Social security contributions; Compulsory health insurance